2015
DOI: 10.4236/ajcm.2015.54039
|View full text |Cite
|
Sign up to set email alerts
|

A New One-Twelfth Step Continuous Block Method for the Solution of Modeled Problems of Ordinary Differential Equations

Abstract: In this paper, we developed a new continuous block method by the method of interpolation and collocation to derive new scheme. We adopted the use of power series as a basis function for approximate solution. We evaluated at off grid points to get a continuous hybrid multistep method. The continuous hybrid multistep method is solved for the independent solution to yield a continuous block method which is evaluated at selected points to yield a discrete block method. The basic properties of the block method were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 4 publications
0
2
0
Order By: Relevance
“…According to Areo and Omojola [21], the linear hybrid multistep method is said to be consistent if all the following four conditions are satisfied i the order of the method must be greater than or equal to one i.e. (p ≥ 1).…”
Section: Consistency Of the New Methodsmentioning
confidence: 99%
“…According to Areo and Omojola [21], the linear hybrid multistep method is said to be consistent if all the following four conditions are satisfied i the order of the method must be greater than or equal to one i.e. (p ≥ 1).…”
Section: Consistency Of the New Methodsmentioning
confidence: 99%
“…The RAS of the developed schemes is considered in the light of Lambert [23]; Areo and Omojola [24]; Ibijola, et al [25].…”
Section: Region Of Absolute Stabilitymentioning
confidence: 99%
“…Because of sufficient stability properties in hybrid block methods as a result of fixed step discretization, ability to use smaller step-sizes for approximations without error growth resulting from perturbation, they have been widely used for solving third order ordinary differential equations (ODEs) (see, Duromola (2019Duromola ( ), modebei et al, (2021, Haweel et al, (2021), Lawal et al, (2018), Aigbiremhon et al, (2021) and Obarhua & Kayode (2016), among others. Also, hybrid numerical methods have been used for the approximations of higher order ODEs (see, Abolarin et al, (2020) and Areo & Omole (2015)) and results from their applications showed improved absolute errors. Similarly, adaptive polynomial method was formulated and implemented on linear, non-linear and a thin film flow problem and compared with some other hybrid block methods (see, Momoniat andMahomed (2010), Mecheel et al, (2013) and Yap et al, (2014)).…”
Section: Introductionmentioning
confidence: 99%